2005
DOI: 10.1002/ajmg.c.30058
|View full text |Cite
|
Sign up to set email alerts
|

Beckwith–Wiedemann syndrome

Abstract: Beckwith-Wiedemann syndrome (BWS) is a clinically heterogeneous overgrowth syndrome associated with an increased risk for embryonal tumor development. BWS provides an ideal model system to study epigenetic mechanisms. This condition is caused by a variety of genetic or epigenetic alterations within two domains of imprinted growth regulatory genes on human chromosome 11p15. Molecular studies of BWS have provided important data with respect to epigenotype/genotype-phenotype correlations; for example, alterations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
201
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 270 publications
(209 citation statements)
references
References 94 publications
5
201
0
3
Order By: Relevance
“…No member of the TNDM or control cohorts showed methylation variation at BWS DMR1, while some BWS patients, as expected (Cooper et al 2005;Weksberg et al 2005), did exhibit gain of methylation at BWS DMR1 (data not shown). To determine whether the LOM at the KCNQTOT1 DMR extended to other imprinted genes, these patients were epigenotyped by MS-PCR for the Prader-Willi/Angelman syndrome imprinted region on chromosome 15 (Zeschnigk et al 1997).…”
Section: Resultsmentioning
confidence: 58%
See 1 more Smart Citation
“…No member of the TNDM or control cohorts showed methylation variation at BWS DMR1, while some BWS patients, as expected (Cooper et al 2005;Weksberg et al 2005), did exhibit gain of methylation at BWS DMR1 (data not shown). To determine whether the LOM at the KCNQTOT1 DMR extended to other imprinted genes, these patients were epigenotyped by MS-PCR for the Prader-Willi/Angelman syndrome imprinted region on chromosome 15 (Zeschnigk et al 1997).…”
Section: Resultsmentioning
confidence: 58%
“…While IUGR is a major feature of TNDM, the imprinting disorder Beckwith-Wiedemann syndrome (BWS) is chiefly characterised by foetal and/or postnatal overgrowth, with variable features including hemihypertrophy, macroglossia, abdominal wall defects and transient hypoglycaemia (reviewed in Weksberg et al 2005;Cooper et al 2005). The BWS locus is an imprinted region of chromosome 11p15 which contains two differentially methylated regions (the H19 and KCNQTOT1 DMRs); a minority of cases involve gene mutation or chromosomal rearrangement, but the major cause ($50%) is epigenetic: LOM at the centromeric KCNQTOT1 DMR which lies within the gene KCNQ1.…”
Section: Introductionmentioning
confidence: 99%
“…Transcription: DNMT3A, DNMT3B, HMT1 and ILF3 (Bermejo-Alvarez et al 2008b) Gene ontology in embryos (Bermejo-Alvarez et al 2010a) and differentiated cells (Wijchers et al 2010) DNA methylation levels in embryos (Bermejo-Alvarez et al 2008b, Gebert et al 2009), ES (Zvetkova et al 2005) and differentiated cells (Tsai et al 2009, Wijchers et al 2010 Long-term effects for DNA methylation-related disorders (Fernandez-Gonzalez et al 2004, Sjoblom et al 2005, Weksberg et al 2005) Long-term effects of periconceptional methyl-deficient maternal diet (Sinclair et al 2007) Protein metabolism Gene ontology (Bermejo-Alvarez et al 2010a) Long-term effects of periconceptional low-protein maternal diet (Kwong et al 2000, Watkins et al 2008) Amino acid turnover (Sturmey et al 2010) Consequences of early embryo sexual dimorphism study associated suboptimal in vitro culture conditions with increased body weight and decreased relative brain size in males, but not in females (Sjoblom et al 2005). In humans, Beckwith-Wiedemann syndrome (BWS) is an overgrowth syndrome demonstrating heterogeneous epigenetic alterations of two imprinted domains on chromosome 11p15, which originate during the preimplantation period, and it has been related with altered methylation patterns in the DMRs regulating a cluster of imprinted genes including some involved in IGF2 signaling.…”
Section: Implications For the Developmental Origins Of Health And Dismentioning
confidence: 99%
“…In humans, Beckwith-Wiedemann syndrome (BWS) is an overgrowth syndrome demonstrating heterogeneous epigenetic alterations of two imprinted domains on chromosome 11p15, which originate during the preimplantation period, and it has been related with altered methylation patterns in the DMRs regulating a cluster of imprinted genes including some involved in IGF2 signaling. A high frequency in monozygotic twins has been reported; with few exceptions, these twins are discordant for BWS and females (Weksberg et al 2005).…”
Section: Implications For the Developmental Origins Of Health And Dismentioning
confidence: 99%
“…In Beckwith-Wiedemann Syndrome, there is a loss of the maternal locus and a gain in the paternal locus. As a consequence, IGF-2 which is expressed on the paternal allele is over-represented whereas p57kip2 and H19 which are expressed on the maternal allele are defective [79].…”
Section: Adrenal Cortical Tumors In Familial Cancer Susceptibility Symentioning
confidence: 99%